2021
DOI: 10.1111/ppc.12961
|View full text |Cite
|
Sign up to set email alerts
|

Digital addiction, academic performance, and sleep disturbance among nursing students

Abstract: Purpose: This study aimed to examine the relationship between digital addiction, academic performance, and sleep disturbance among nursing students.Design and methods: The study was a correlational and cross-sectional design. Four hundred twenty-nine nursing students were enrolled in this study. Findings: There was a positive significant relationship between the mean Sleep Disturbance (SD) T-scores and Digital Addiction Scale (DAS) scores (r = 0.203, p < 0.01). Furthermore, a positive correlation was found bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…This invited talk highlights the importance of involving the software engineering community in designing conscious and conscious use of technology. Aktas, et al (2022) aimed to examine the relationship between digital addiction, academic performance and sleep disturbance in nursing students. The study included 429 nursing students and used a relational and crosssectional design.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This invited talk highlights the importance of involving the software engineering community in designing conscious and conscious use of technology. Aktas, et al (2022) aimed to examine the relationship between digital addiction, academic performance and sleep disturbance in nursing students. The study included 429 nursing students and used a relational and crosssectional design.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 7 Insomnia is related to an increased risk of psychiatric problems such as attention and behavioral problems, impulsivity, impaired social functioning, and digital addiction. 8 - 10 There are some objective methods for evaluating insomnia. Polysomnography and wrist actigraphy are the main objective methods, but they are time-consuming and require equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Poor sleep quality can have an impact on individuals of all ages and populations [1], and particularly health science students, whose academic careers are highly stressful [2]. A recently published umbrella review reported a prevalence of self-reported sleep problems in medical and nursing students between 40 and 55% [3][4][5][6][7][8]. The prevalence of sleep problems among medical students varies across countries; for example, in China, the prevalence seems to be as low as 25% [9,10], while Iran had the highest prevalence of around 58% [11].…”
Section: Introductionmentioning
confidence: 99%